Cover Feature: Composition‐Controlled Synthesis of Hybrid Perovskite Nanoparticles by Ionic Metathesis: Bandgap Engineering Studies from Experiments and Theoretical Calculations (Chem. Eur. J. 42/2019). Issue 42 (14th June 2019) - Roy, Mrinmoy; Vikram; Banerjee, Sucheta; Mitra, Arijit; Alam, Aftab; Aslam, M.
Abstract : Color‐map variation shown in the cover artwork illustrates possible Cl/Br/I binary mixing; the resultant bandgap was recorded using an unconventional low‐cost approach to synthesize pure/mixed hybrid lead halide perovksite nanoparticles. The glow represents the high quantum yield emission for these nanoparticles. Theoretical calculations support the superiority of the proposed synthesis method over conventional ones. More information can be found in the Full Paper by A. Alam, M. Aslam, et al. on page 9892 .